2021
DOI: 10.1002/anbr.202100039
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Multimodel Zirconia Nanosystems for High‐Performance Biomedical Applications

Abstract: Advancement in nanotechnology supports system development to achieve rapid, affordable, and intelligent health management and has raised the urgent demand to explore multimodel affordable metal oxide nanostructures with the features of biocompatible tunable performance and scaled‐up processing. Keeping this as a motivation, zirconia nanostructures (Zr‐NSs) are emerging as nanostructures of choice for advanced biomedical applications due to affordable, scalable production, easy surface modifications, tunable su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 345 publications
0
13
0
Order By: Relevance
“…According to the Randles-Sevcik equation (Wang, 2000), Figure 9 shows a linear plot of Ipc and Ipa versus ν 1⁄ 2 , for the PB-fCNT/TiO 2 .ZrO 2 (36)500 °C.20/GC electrode, revealing a diffusion-controlled process, which we have related to the slow diffusion of potassium ions in the lattice of the film on the electrode (Karyakin, 2001). 36)500 °C.20/GC electrode with the prepared electrodes under the same conditions with the individual oxides in their structure (Li et al, 2007;Rathee et al, 2021). The surface concentration (Γ c ) of PB on the modified electrode was evaluated from the slope I p /A versus ν, according to the following equation (Tang et al, 1994;Du et al, 2010):…”
Section: Electrochemical Characterizationmentioning
confidence: 79%
See 1 more Smart Citation
“…According to the Randles-Sevcik equation (Wang, 2000), Figure 9 shows a linear plot of Ipc and Ipa versus ν 1⁄ 2 , for the PB-fCNT/TiO 2 .ZrO 2 (36)500 °C.20/GC electrode, revealing a diffusion-controlled process, which we have related to the slow diffusion of potassium ions in the lattice of the film on the electrode (Karyakin, 2001). 36)500 °C.20/GC electrode with the prepared electrodes under the same conditions with the individual oxides in their structure (Li et al, 2007;Rathee et al, 2021). The surface concentration (Γ c ) of PB on the modified electrode was evaluated from the slope I p /A versus ν, according to the following equation (Tang et al, 1994;Du et al, 2010):…”
Section: Electrochemical Characterizationmentioning
confidence: 79%
“…The combination of PB with CNTs and nanostructured metal oxides ( Roushani et al, 2013a ; Roushani et al, 2013b ; Salimi et al, 2013 ; Roushani and Karami, 2014 ; Roushani and Dizajdizi, 2015 ; Roushani and Dizajdizi, 2016 ) can generate novel results for good electrical communication between the recognition system and the electrode surface. Zirconium oxide (ZrO 2 ) nanoparticles have been used as an electrochemical biosensor platform for oral cancer detection by cyclic voltammetry ( Zong et al, 2007 ; Zhao et al, 2020 ; Rathee et al, 2021 ). A nanostructure material from ZrO 2 nanoparticles on CNTs was used to immobilize myoglobin showing excellent electrocatalytic activity for the reduction of H 2 O 2 ( Yang et al, 2020 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The dispersed metal oxide on the RGO sheet will be helpful in reducing steric hindrance produced between the biomolecules. [28][29][30] Also, the electrochemical performance is known to be enhanced when using a conductive and large surface area support for metal oxides. 20,21,30 A RGO supported nZrO 2 nanoparticle based biosensing platform has been successfully employed for enzyme immobilization and utilized for chlorpyrifos pesticide detection.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Also, the electrochemical performance is known to be enhanced when using a conductive and large surface area support for metal oxides. 20,21,30 A RGO supported nZrO 2 nanoparticle based biosensing platform has been successfully employed for enzyme immobilization and utilized for chlorpyrifos pesticide detection. 21 Gupta et al showed an improvement in electrochemical characteristics and low aggregation of ZrO 2 nanoparticles by employing a ZrO 2 -RGO nanocomposite for the detection of ochratoxin A.…”
Section: Introductionmentioning
confidence: 99%
“…Signal amplification strategies using nanomaterials as electrode materials, carriers, labels, or catalysts have been previously employed to improve the sensitivity of electrochemical sensors. Due to their capability to enhance electronic conductivity between electrodes and biomolecules, various nanosized metal oxides are often used to construct biosensor interfaces . Among them, the nanostructured transition metal oxide, zirconia (ZrO 2 ), has sparked credible interest due to its thermal stability, chemical inertness, nontoxicity, wide band gap, and superior electrical and surface properties As a result, it has been reported to possess applications in a range of fields, including orthopedic implants, tissue engineering, biosensing, and bioimaging . However, bare ZrO 2 nanoparticles (NPs) tend to aggregate and form large clusters during synthesis, which negatively impacts upon their application potential.…”
Section: Introductionmentioning
confidence: 99%